Reducing Wastage In Electricity Usage Through The Use Of Advancement In GSM Technology - Adetona, S.O.; Ogundeji, A.O.; Ipinnimo, O.; Salawu, R.I. (Journal of Engineering and Technology (JET), 2020)
Due to epileptic nature of electricity in developing economy like Nigeria, people have their electrical loads on mistakenly when leaving homes for offices or offices for homes; and this normally resulting in energy wastages and inefficiencies. These wastages are very detrimental to industrial development; therefore, there is need to make use of advancement in technology to reduce wastage in electricity usage. To that effect, this paper proposes a device that can control home appliances via Global System for Mobile Communication network so as to reduce electrical energy wastages and consequently, enhance industrial sectors growth. In addition, the proposed device will inform the user when utility board restores electricity on the user’s mobile line, display on the mobile line of the user the states of all the connected appliances and receive appropriate command from the user, to either switch ON or OFF specified appliance(s). The various results obtained when the proposed device was tested revealed that it worked according to the design specifications.